Doctoral Education as an Institutional Resource for Training Research and Higher Education Personnel (Article 1) - B. I. Bednyi; A. A. Mironos; N. V. Rybakov (Высшее образование в России, 2019)
The diversification of professional trajectories of academic degree holders is now becoming a global trend, and it prompts us to take a fresh look at the problem of evaluating the effectiveness of existing institutions for the training of academic and research personnel – the systems of doctoral education in Russia and abroad – in terms of the training of academic researchers and higher education teaching staff. Our two articles which share the scope of problems and have a single general concept, consecutively address the following issues: the collection and analysis of empirical data on training in doctoral programs; the dynamics of dissertation defense by graduates after the completion of doctoral programs; the actual timeframe of doctoral students’ advancement to their degree; the proportion of graduates who continue their scientific career after graduating from the doctoral program. The first article analyzes the organizational and methodological aspects of information and analytical support of institutions responsible for doctoral education in the countries of the European Union, the United States and Russia. It provides information about the organization of the systems for monitoring doctoral education and doctoral program graduates’ professional careers in foreign countries. The authors note the insufficient information support for the programs aiming to develop doctoral education in Russia, as well as the lack of empirical data necessary to assess the effectiveness of Russian doctoral education in the reproduction of human resources for the research and education sector. The results of the authors’ scientometric research concerning doctoral program graduates’ retention in the field of research and higher education are announced. The second article will present the details of the method and the results of these studies.